1988
DOI: 10.1021/ac00169a026
|View full text |Cite
|
Sign up to set email alerts
|

Highly fluorinated stationary phases for analysis for polyfluorinated solutes by reversed-phase high-performance liquid chromatography

Abstract: Two perfluorinated stationary phases were prepared by reacting two perfluoroalkyl amlnosilanes (RFC2H4SI(CH3)2N-(CH3)2 with Rf = C8F17 or C10F21) with Lichrosorb S1100 (10 µ ). The chromatographic properties of such stationary phases were checked with perfluoroalkylated series and corresponding hydrogenated series of compounds and compared with a classical C18 stationary phase. The perfluoroalkylated series Included Iodides (RFI), iodoethanes (RFCH2CH2I), and ethenes (RFCH=CH2), RF ranging from C2F5 to C10F21.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
1
16
0
Order By: Relevance
“…One can conclude that using this hydro-organic mobile phase, seven CF2 or CF3 increments are equivalent to nine CH2 or CH 3 increments and that six CF2 or CF 3 increments with an oxygen atom replaced by a sulfur atom are equivalent to eight CH2 or CH3 increments. The greater retention of the perfluorinated surfactants in comparison with the perhydrogenated surfactants corroborates RPLC results published by Krafft [21] for perfluorinated iodides and by Gilpin [22] for perfluoroalkanoate esters. For better comparison of compound hydrophobicity, which can be independent of mobile-phase composition, parameters log kw and m corresponding to the linear relationship given by Eq.…”
Section: Comparison Of Chromatographic Behaviorsupporting
confidence: 89%
“…One can conclude that using this hydro-organic mobile phase, seven CF2 or CF3 increments are equivalent to nine CH2 or CH 3 increments and that six CF2 or CF 3 increments with an oxygen atom replaced by a sulfur atom are equivalent to eight CH2 or CH3 increments. The greater retention of the perfluorinated surfactants in comparison with the perhydrogenated surfactants corroborates RPLC results published by Krafft [21] for perfluorinated iodides and by Gilpin [22] for perfluoroalkanoate esters. For better comparison of compound hydrophobicity, which can be independent of mobile-phase composition, parameters log kw and m corresponding to the linear relationship given by Eq.…”
Section: Comparison Of Chromatographic Behaviorsupporting
confidence: 89%
“…Fluorinated-bonded-silica-based stationary phases have been commonly used in the reversed phase separations in HPLC [41][42][43][44][45][46][47]. In these studies, the retention properties of fluorinated phases synthesized with different methods were investigated [41][42][43][44][45][46][47].…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, the retention properties of fluorinated phases synthesized with different methods were investigated [41][42][43][44][45][46][47]. Several studies were also performed on the electroosmotic and retention properties of fluorinatedbonded silica-based particulate stationary phases in electrochromatographic separations [48,49].…”
Section: Resultsmentioning
confidence: 99%
“…In 1983, Xindu and Carr [29] reported the application of FluoroFlash and FluoroSep-RP Octyl (C 8 F 17 ) for the analysis of proteins using a high percentage of organic modifier in the mobile phase. In 1988, Kraff et al [30] showed that polyfluorinated analytes were better retained on alkyl fluorinated stationary phases and a study by Billiet et al [31] observed enhanced selectivity for some esters and ketones on a fluorinated alkyl phase. Pentafluorophenyl silica bonded phases have been found to possess enhanced retention and special selectivity for aromatic compounds compared to phenyl phases [32,33].…”
Section: Introductionmentioning
confidence: 99%